The Incomprehension of Terror as a Harbinger of “Post-Truth”? - Shor-Chudnovskaya, Anna (Stan Rzeczy, 2019)
This article is devoted to the attitude to truth as a part of political epistemology and of political culture in post-Soviet Russia. It considers the extent to which the Great Terror contributed to the development of a specific political epistemology, which is also largely characteristic of later periods of Soviet history and perhaps even of today. Of particular interest is the population’s perception of the terror as inaccessible or poorly accessible to logical understanding. As main sources, the article relies on two literary texts: Lydia Chukovskaya’s Sofia Petrovna and Veniamin Kaverin’s The Open Book. Despite all the apparent differences between the Soviet system and today’s Russia, one important similarity is striking: over the last two decades (after 1999) there has been a visible increase in the belief that it is impossible for a political subject to separate truth from lying and that the sphere of public administration and political interests is, by definition, a place where deception prevails. This article discusses the potential historical roots of this certainty.